Cytokine profile in the patients with bronchial asthma of different endotypes after vaccination against pneumococcus - A. M. Kostinov; A. Yu. Konishcheva; A. D. Protasov; M. P. Kostinov (Медицинская иммунология, 2025)
Numerous observations of patients with bronchial asthma (BA) vaccinated against pneumococcal infection have revealed a significantly reduced frequency of exacerbations and hospitalisations after immunisation. Several studies have considered pneumococcal vaccines potential immunoregulators that may improve the clinical course of BA via modulation of the immune response. However, interpretation of these results has serious limitations due to heterogeneity of primary disease and differences in vaccine preparations. The aim of the present study was to perform a comparative analysis of the key cytokines levels which characterize development of distinct BA endotypes in patients following administration of conjugated pneumococcal vaccine. We have analyzed serum samples (n = 31) from patients with BA immunized by PCV13 (Prevenar 13), using ELISA technique, for Th1/Th2/Treg cytokines (IFNγ, IL-4, IL-6, IL-8, IL-10, IL-18, TNFα, and MCP-1), and total IgE level. The time points of sampling were as follows: initial terms, 6 weeks, 6 and 12 months after vaccination.The results of the study indicate that vaccination against pneumococcal infection using a PCV13 in patients with BA was accompanied by high clinical efficacy, regardless of the disease endotype. This finding was evidenced by a decreased number of BA exacerbations in the patients, and an increased number of non-hospitalized BA patients during 1 year of observation. The clustering of patients according to their inflammatory profile enabled us to detect specific patterns of the cytokine profile. These changes included a statistically significant increase in the concentration of IFNγ in blood serum at 6 weeks after immunisation in the patients with the T2-“high” asthma endotype. Statistically significant changes were observed in patients with atopy and elevated total IgE levels in serum, who exhibited a peak increase in IFNγ concentration, also 6 weeks after vaccination. Conversely, no significant changes in cytokine levels were observed in patients with T2-“low” asthma endotype within a year after vaccination. The results of the study demonstrate that IFNγ plays a significant role in the potential adjustment of immunity in the patients with T2-«high» asthma endotype following immunisation with a pneumococcal conjugate vaccine.